Evaluation and Optimization of Vaccine Priming in Dogs against Rabies - Sowmiya, M.; M.Asokkumar; S.Rathna Praba; T.Devi (The Indian Veterinary Journal, 2026)
Vaccination of dogs against rabies is fundamental for rabies control since the dog is the main reservoir and transmitter of rabies in India. Though the young puppies are generally primed with rabies vaccine when they attain three months of age, a few cases of puppies aged below 2 months old were presented to the Rabies Surveillance Unit, Madras Veterinary College Teaching Hospital, which showed positive for rabies by FAT. This study was designed to assess the maternal-derived antibody status of puppies from vaccinated and unvaccinated bitches (Group I and II), and the dynamic status of rabies virus neutralizing antibody in adult dogs (Group III: one year after primary vaccination, Group IV: Regularly vaccinated adults and Group V: Irregularly vaccinated adults). Longitudinal vaccine efficacy was also studied to elucidate the frequency and magnitude of Rabies Virus Neutralization Antibody (RVNA) in pre-exposure prophylaxis (PrEP; Groups VI and VII). Each group comprised 18 healthy dogs, vaccinated with inactivated vaccine and blood samples were collected on 0, 21, 90 and 180 days post vaccination (dpv0, 21, 90 and 180) for PrEP, and the serum neutralizing rabies antibody titres were assessed by Rapid Fluorescent Foci Inhibition Test (RFFIT). In the pre-exposure study, all puppies in both groups had insignificant antibody titre on day 0, which evidenced the waned status of maternal-derived antibody at 12 weeks of age. The dogs that received the prime-boost dose resulted in maintaining the protective titre (≥0.5 IU/mL) in all immunized dogs on dpv180, with a mean titre of 7.09±0.83, whereas primovaccinated dogs resulted in having protective titre only in 88.88 per cent of immunized dogs with a mean titre of 1.94±0.34. Since the level of maternal-derived antibodies, even in puppies born to vaccinated bitches are insignificant at 10 to 12 weeks of age, the immunization strategy against rabies in puppies warrants the advancement of priming age with one booster vaccine at a suitable interval of 3 to 4 weeks to achieve the population immunity in view of effective containment of rabies spread.